RULERS DESTRUCTIVE PRACTICES VIA BULL SYMBOL - TURAN, Fulya (Atlas Journal, 2022)
In this study, power and rulers oppressive practices are visualized with “bull” and its associations. Throughout the history, bull has been an attractive figure of power and governance and has named some powerful animals; the names of equipment that razes nature to the ground are inspired by it. Bull has been an interesting figure in art history as a symbol of power; and has also been mentioned as oppressive in addition to symbolizing masculine power. Although there have been many artworks and artists related with bull in art history, this study examines only Suit Vollard of Picasso. Our time has been documented by the images of the "Demolition" and "Good Night" series that contain power and governance symbols visualized by the bull and its associations. The conceptually strong new narrative language that has started and shaped with the demolition series is named as "Materialist Synthetic Reality". Collage is used as narration, and oil painting on canvas is used as material. The hope sought was found in the Seville Declaration on Violence by UNESCO in 1986. Finally, legitimating rulers oppressive practices via association with attributes of bulls has been rejected and a call for wake up and responsibility has been made.